Mediating role of stakeholder expectations on relationship between strategic corporate social responsibility and firm performance in manufacturing firms in China - Fu, Hongyan (2017)
This study examined the relationship between strategic CSR and firm performance and explores the role of stakeholder expectations as a mediator between these two variables. The moderating effect of firm size on the relationship between strategic CSR and firm performance was also examined. Mixed methods were adopted to accomplish this task; semi-structured interviews method was conducted to identify stakeholder CSR expectations for two primary stakeholder groups, employees, and customers. Furthermore, surveys were used to test the hypothesised relationships in this study. Interviews were conducted on 29 respondents from Yingli Green Energy (YGE) and Great Wall Motor, China. The themes identified from the interviews were used in the development of the questionnaire. Data was collected from a sample of 1749 manufacturing firms listed in the Shanghai Stock Exchange. At the end of the data collection period, 433 questionnaires were received. However, only 403 were usable. The Partial Least Square Structural Equation Modeling (PLS-SEM) approach was used to analyse the data. The results confirmed that strategic CSR significantly influenced a firm’s performance (both financial and non-financial) and this relationship was mediated by stakeholder expectations. This study shows the mediating effect of stakeholder expectations underlying the strategic CSR-firm performance relationship. In other words, firm performance will improve when a firm’s CSR activities meets its stakeholder’s expectations. However, firm size was not a significant moderator. Future longitudinal and experimental research would help to confirm the causal paths investigated in the present study.